P48 But what happens in a Hospice? Interprofessional learning in the workplace. (1st October 2013) - Taplin, Sue
Abstract : Building on established links between the University of Leicester Medical School, the School of Social Work and LOROS the Leicestershire Hospice, an interprofessional learning module has been developed which enables social work students on the MA programme at the University of Leicester to experience two days in the life of a Hospice. This programme, which has now been running for five years, gives social work students the opportunity to meet and learn from different members of the hospice mutidisciplinary team, through a variety of means, including group work, question and answer sessions, meeting informal carers who talk about their experiences of looking after someone at the end of life and a guided tour of the hospice. Although the programme can vary from year to year according to the availability of different members of staff, there is always a session on the role of the social worker in end-of-life care, with teaching on handling difficult situations, exploring the meaning to individuals of loss and change and managing your own emotions in this sensitive and emotional area of practice. The sessions are generally very well evaluated: feedback comments from recent sessions include the following: "the carer was very inspiring and it was helpful to hear first-hand experience"..."very upsetting at times but have taken a lot from the experience nonetheless"..."especially enjoyed the talk regarding spirituality" It has always proved important to discuss the sessions with the Interprofessional Learning Co-ordinator in the School of Social Work at the University to see if there have been any changes to the core teaching programme, in order that we can ensure that the sessions are covering new ground for the students and enhancing their learning about hospice care, which we believe is a life lesson for all.